Potential inappropriate prescribing among ambulatory elderly patients in a geriatric centre in southwestern Nigeria: Beers criteria versus STOPP/START criteria (2020)
Purpose: To identify potentially inappropriate prescribing in ambulatory elderly patients and compare the appropriateness of guidelines; Beers' and Screening Tool of Older Person’s Prescription (STOPP)/ Screening Tool to Alert Right Treatment (START) criteria to detect potentially inappropriate prescribing among the elderly. Methods: A retrospective study was conducted using case files of 335 elderly patients aged ≥ 60 years between 1st January and 31st December 2016, using a data extraction sheet. The 2015 American Geriatrics Society (AGS)-Beers Criteria, and version 2 of the STOPP and START were subsequently used to identify the Potentially Inappropriate Prescribing (PIP) and Potential Prescribing Omissions (PPOs). Results: Mean age of patients was 69 ± 0.4 years (range 60 - 85 years) and 219 (65.4 %) were females. An average of 4.2 medications per patient prescription was found. The Beers criteria identified 26.5 % PIP, while STOPP criteria identified 57.1 % PIP. START detected 29 PPOs in 15 (4.4 %) of the patient’s prescription. The most prevalent disease conditions were hypertension 235 (70.1 %) and osteoarthritis 64 (19.3 %). Polypharmacy was significantly associated with PIP in both Beers (p = 0.002) and STOPP (p = 0.001) criteria. Conclusion: The prevalence of PIP is high among elderly patients. The STOPP/START criteria identified a higher proportion of PIP among elderly patients compared with Beers criteria. The frequency of PIP should stimulate efforts to curtail potentially inappropriate prescribing and may require the need for advocating for a national criterion to be adopted by health care professionals in Nigeria.